2008
DOI: 10.1108/15982688200800017
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Environmental Management Investment Allocation

Abstract: The 21st century is a new century of environmental protection. Environmental protection is one of the most important subject matters yet to come. Moreover, as the public pays more attention to environmental problems, enterprises should increase their investment in environmental management. Therefore, determining the investment level for environmental management and allocating the investment to associated environmental management activities has become a major task. The principal and agent theory and sales respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Specifically, Tien et al (2008) provided an integrated decision-making method (i.e., the optimal allocation decision) relative to the decision-making in respect of environmental investment levels and found that enterprise sales and profits responded better to the optimal allocation than to the allocation by ratio. Furthermore, increasing the consumers' recognition and approval of environmental investment, environmental investment efficiency, and production efficiency will be conducive to enhancing the environmental investment level (Tien et al, 2008).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Tien et al (2008) provided an integrated decision-making method (i.e., the optimal allocation decision) relative to the decision-making in respect of environmental investment levels and found that enterprise sales and profits responded better to the optimal allocation than to the allocation by ratio. Furthermore, increasing the consumers' recognition and approval of environmental investment, environmental investment efficiency, and production efficiency will be conducive to enhancing the environmental investment level (Tien et al, 2008).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Furthermore, increasing the consumers' recognition and approval of environmental investment, environmental investment efficiency, and production efficiency will be conducive to enhancing the environmental investment level (Tien et al, 2008).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%